Konjac glucomannan-modified ferrous fumarate emulsions with interpenetrating polymer networks: Physicochemical stability, microstructure, and bioaccessibility - Tianyu Zhang; Fengru Zhang; Xintong Wang; Yuanting Wang; Mengting Jia; Zihan Ma; Yanbo Wang; Duoxia Xu (Food Hydrocolloids, 2027)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

Robust prediction of CO2 absorption in blended amines via structure-concentration integration: A machine learning approach for imbalanced and data-scarce systems - Binmin Li; Tengxian Qin; Zehua Xu; Zhi Yang; Guiyang Ye; Jiaoying Huang; Yuanting Qiao; Xuelan Zeng; Song He; Yawen Zheng; Junyao Wang (Journal of Environmental Chemical Engineering, 2026)

Sea trial of anti-rolling performance of a zero-speed ship model in coastal waves using PPO-based reinforcement learning control of flapping fins - Yuanting Zou; Wenhua Xu; Jialong Jiao (Ocean Engineering, 2026)

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

Polyphenol-mediated hierarchical porous hydrogel evaporators for accelerated water transport and reduced evaporation enthalpy - Xueqian Zhang; Hongtao Li; Bo Liang; Zikun Zou; Zhen Yang; Shaohui Xiong; Lei Yang; Xu Wang; Yang Chen; Yuanting Xu; Yiwen Li (Science Bulletin, 2026)

Experimental investigation of anti-roll performance of a ship with flap-type fin stabilizers in oblique waves at zero speed - Jialong Jiao; Yuanting Zou; Wenhua Xu; Zheng Yang (Ocean Engineering, 2025)

Mechanistic insights into ozone-induced asthma exacerbation: role of oxidative stress and IL-33 - Xinyi Fang; Bin Pan; Yuanting Xie; Wenpu Shao; Jingyu Li; Dongyang Han; Xiaoqing Hong; Wenyue Tu; Yifan Zhao; Jiaojiao Wu; Yaning Zhu; Yubin Zhang; et al. (Journal of Hazardous Materials, 2025)

Adsorption of radioiodine by metal sulfides and relevant derivatives - Wei Zheng; Xiaoxuan Chen; Hao Xu; Duxia Li; Yuanting Zhang; Wanliang Yang; Meisong Xu; Dehong Gong; Mengkui Tian (Journal of Cleaner Production, 2025)

Hollow Fe2O3-NiFe2O4 hetero-nanoframes coupled with N-doped graphene for boosted electrochemical water oxidation through optimizing intermediate bonding - Yuanting Li; Ya Zhang; Ruidong Shi; Xiaoxin Xu; Xue Wang; Gongbing Zhou (Chemical Engineering Journal, 2025)

Intelligent control of flap-type fin stabilizer for ship roll motion reduction - Wenhua Xu; Jialong Jiao; Guodong Xu; Miao Zhang; Yuanting Zou (Ocean Engineering, 2025)

Differentiation and characterization of non-thymomatous ocular myasthenia gravis children with CT - Youran Cai; Zhongyuan Cheng; Yuanting Yang; Baojun Xu; Qiwen Feng; Xu Liu; Jian Chen; Qing Zhou (Acta Neurologica Belgica, 2025)

Exploring the response and prediction of phytoplankton to environmental factors in eutrophic marine areas using interpretable machine learning methods - Shimin Yang; Yuanting Ma; Jie Gao; Xiajie Wang; Futian Weng; Yan Zhang; Yan Xu (Science of The Total Environment, 2024)

Gut microbiota mediates ambient PM2.5 exposure-induced abnormal glucose metabolism via short-chain fatty acids - Wenpu Shao; Bin Pan; Zhouzhou Li; Renzhen Peng; Wenhui Yang; Yuanting Xie; Dongyang Han; Xinyi Fang; Jingyu Li; Yaning Zhu; Zhuohui Zhao; Haidong Kan; et al. (Journal of Hazardous Materials, 2024)

Enhanced dewatering of dredging slurry by Fenton preoxidation and composite coagulants: optimization experiments and dewatering mechanisms - Xuyang Zhou; Jingwei Feng; Liu Zhang; Yulin Yang; Yuanting Xiao; Chunli Fan; Deqian Xu; Aiyong Zhang (Environmental Science and Pollution Research, 2024)

Promotion of manganese on Fe-based catalyst for the production of carbon nanotubes (CNTs) from plastics - Su He; Chunchun Li; Hongman Sun; Christopher M.A. Parlett; Yuanting Qiao; Youhe Wang; Yikai Xu; Ningbo Gao; Chunfei Wu (Chemical Engineering Journal, 2024)

Azobenzene-equipped Covalent triazine polymers for Visible-Light-Driven photocatalytic reduction of CO2 to CH4 - Qi Huang; Zhen Zhan; Yuanting Qiao; Xueting Pan; Shaojun Xu; Bien Tan; Chunfei Wu (Fuel, 2024)

Asymmetric phosphorylation integrating host feature and blue thermally activated delayed fluorescence of thiaxanthene S,S-dioxide emitter for efficient heavily doped white organic light-emitting diodes - Yingying Chen; Chao Wang; Peng Ma; Yuanting Guo; Yuetong Liu; Aiqi Dang; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Preparation of high-performance asymmetric supercapacitors based on NiCo2S4 nanospheres and CuO-MOF nanosheets on carbon fibers - Baopeng Liu; Jun Zhang; Jiawei Xu; Yanjie Pan; Yanshan Huang; Sheng Han; Yuanting Li (Fuel, 2024)

Cholinergic anti-inflammatory pathway mediates diesel exhaust PM2.5-induced pulmonary and systemic inflammation - Yuanting Xie; Shimin Tao; Bin Pan; Wenhui Yang; Wenpu Shao; Xinyi Fang; Dongyang Han; Jingyu Li; Yubin Zhang; Renjie Chen; Weihua Li; Yanyi Xu; et al. (Journal of Hazardous Materials, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

Toxicity effects of disinfection byproduct chloroacetic acid to Microcystis aeruginosa: Cytotoxicity and mechanisms - Jing Ye; Jiawei Ni; Fuxiang Tian; Xiyan Ji; Meifang Hou; Yuanting Li; Lei Yang; Runxiang Wang; Wenwu Xu; Liang Meng (Journal of Environmental Sciences, 2023)

Adaption of tobacco rattle virus to its solanaceous hosts is related to the codon usage bias of the hosts and that of the viral 16 K gene - Qi Lin; Yuanting Zheng; Yueyan Yin; Yi Chen; Miaomiao Li; Hongying Zheng; Jianping Chen; Fei Yan; Yuwen Lu; Shengchun Xu (European Journal of Plant Pathology, 2023)

Highly active and durable nitrogen-doped CoP/CeO2 nanowire heterostructures for overall water splitting - Lili Zhang; Yuanting Lei; Wenjing Xu; Dan Wang; Yafei Zhao; Wenxing Chen; Xu Xiang; Xinchang Pang; Bing Zhang; Huishan Shang (Chemical Engineering Journal, 2023)

A robust and 3D-printed solar evaporator based on naturally occurring molecules - Xueqian Zhang; Yu Yan; Ning Li; Peng Yang; Yiyan Yang; Gaigai Duan; Xu Wang; Yuanting Xu; Yiwen Li (Science Bulletin, 2023)

Maternal exposure to ambient PM2.5 perturbs the metabolic homeostasis of maternal serum and placenta in mice - Shimin Tao; Mingjun Yang; Bin Pan; Yuzhu Wang; Fang Tian; Dongyang Han; Wenpu Shao; Wenhui Yang; Yuanting Xie; Xinyi Fang; Minjie Xia; Jingying Hu; et al. (Environmental Research, 2023)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.